2023
DOI: 10.3390/jpm13040636
|View full text |Cite
|
Sign up to set email alerts
|

Lower All-Cause Mortality Risk in Females and Males with Peripheral Artery Disease following Pain-Free Home-Based Exercise: A 7-Year Observational Study

Abstract: We evaluated the sex-specific difference in response upon participation in an exercise program with respect to the risk of adverse clinical outcomes among patients with peripheral artery disease (PAD) and claudication. The records of 400 PAD patients were assessed between 2012 and 2015. Two hundred of them were addressed to a walking program prescribed at the hospital and executed at home at symptom-free walking speed (Ex), while the remaining 200 acted as a control group (Co). The number and date of deaths, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 78 publications
2
2
0
Order By: Relevance
“…After six months of performing moderate-intensity physical activity in a nature-based environment, we found that half of the study participants achieved minor improvements, while half of them achieved major improvements in the peripheral pulse characteristics measured by the smart anklet. In line with our results, studies performed in Italy [14][15][16] showed that a structured exercise program resulted in progressive improvement in vascular function and the ability to walk, a lower death rate, and better long-term clinical outcomes, particularly among women, and participants who attained a moderate increase in exercise capacity. Studies from the USA [17,18] demonstrated the effects of exercise rehabilitation in older patients with peripheral arterial occlusive disease and symptomatic and functional improvement in performance parameters.…”
Section: Discussionsupporting
confidence: 91%
“…After six months of performing moderate-intensity physical activity in a nature-based environment, we found that half of the study participants achieved minor improvements, while half of them achieved major improvements in the peripheral pulse characteristics measured by the smart anklet. In line with our results, studies performed in Italy [14][15][16] showed that a structured exercise program resulted in progressive improvement in vascular function and the ability to walk, a lower death rate, and better long-term clinical outcomes, particularly among women, and participants who attained a moderate increase in exercise capacity. Studies from the USA [17,18] demonstrated the effects of exercise rehabilitation in older patients with peripheral arterial occlusive disease and symptomatic and functional improvement in performance parameters.…”
Section: Discussionsupporting
confidence: 91%
“…Different outcomes following rehabilitation programs in chronic diseases have reported in women compared to men, related to interest/motivation, adherence to physical activity or effects achieved [50][51][52][53]. Considering the lower attitude of women toward exercise [50], this observation confirms the findings previously reported after the same home-based program [53] and the results of other authors who reported similar benefits in women compared to men after a low-intensity treadmill program [38,[53][54][55]. To detect the changes occurring in foot perfusion, IRT may be a promising and useful method.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, we noted significant progressively increasing temperature variations at each time point of collection for most of the RoIs in both limbs without sex differences as other outcomes following the same home-based program [ 37 , 38 ]. These observed temperature changes are correlated with the congruent hemodynamic variations occurring in both feet, as measured by ABI, although with a lower coefficient with respect to the 0.7 value previously reported in a population without arterial calcifications [ 14 ].…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, in the home exercise group, women had a higher survival rate (90%) than men (82%). In addition, in comparison to the control group, the group of patients who underwent rehabilitation demonstrated lower rates of long-term hospitalization (88% for women and 89% for men, compared with 66% for women and 68% for men) and amputations (4% for women and 10% for men, compared with 3% for women and 3% for men) [44].…”
Section: Gender-specific Response Differences In Mortality and Clinic...mentioning
confidence: 86%